RANCANG BANGUN UNIVERSAL TOOL BIT UNTUK PENGENCANGAN MUR PENGUNCI TIE ROD - Nugraha, Afitro Adam; Yusak Faqih Wibowo; Yohanes C. Sutama; Ajib Rosadi (Technologic, 2024)
Abstract-- Precise tightening of tie rod lock nuts is a crucial aspect in maintaining the safety and optimal performance of a vehicle's steering system. The primary challenge in this process is the impracticality of tightening using torque wrenches connected to shock wrenches due to limited accessibility and the difficult-to-reach location of the lock nuts. To address this obstacle, researchers have designed an effective solution in the form of a torque wrench extension made from S45C steel. This torque wrench extension allows technicians to tighten tie rod lock nuts that were previously inaccessible using shock wrenches, while also applying the required torque specified for the application. The objective of this study is to evaluate the effectiveness of using the torque wrench extension to enhance the accuracy of tightening tie rod lock nuts at UPT Otomotif Politeknik Astra. Experiments were conducted by applying the torque wrench extension to several vehicles brought into the Automotive workshop at UPT Otomotif Politeknik Astra. Due to the inability to tighten lock nuts with shock wrenches, a direct comparison between the tightening using the torque wrench extension and conventional tightening methods could not be performed on the tie rod lock nuts. Therefore, the comparative tightening was executed on sample nuts. The research findings demonstrate that the utilization of the torque wrench extension significantly improves the accuracy of tightening tie rod lock nuts with lower error rates compared to conventional tightening methods. This discovery suggests the effective application of the torque wrench extension as a solution to enhance the accuracy of tie rod lock nut tightening, not only at UPT Otomotif Politeknik Astra but also at other locations. Implementing the torque wrench extension will effectively contribute to maintaining the safety and optimal performance of a vehicle's steering system while reducing the potential risks arising from improper tightening